Mechanisms of renal NaCl retention in proteinuric disease. (7th January 2013) - Svenningsen, P.; Friis, U. G.; Versland, J. B.; Buhl, K. B.; Møller Frederiksen, B.; Andersen, H.; Zachar, R. M.; Bistrup, C.; Skøtt, O.; Jørgensen, J. S.; Andersen, R. F.; Jensen, B. L.
Abstract In diseases with proteinuria, for example nephrotic syndrome and pre‐eclampsia, there often are suppression of plasma renin–angiotensin–aldosterone system components, expansion of extracellular volume and avid renal sodium retention. Mechanisms of sodium retention in proteinuria are reviewed. In animal models of nephrotic syndrome, the amiloride‐sensitive epithelial sodium channel ENaC is activated while more proximal renal Na+ transporters are down‐regulated. With suppressed plasma aldosterone concentration and little change in ENaC abundance in nephrotic syndrome, the alternative modality of proteolytic activation of ENaC has been explored. Proteolysis leads to putative release of an inhibitory peptide from the extracellular domain of the γ ENaC subunit. This leads to full activation of the channel. Plasminogen has been demonstrated in urine from patients with nephrotic syndrome and pre‐eclampsia. Urine plasminogen correlates with urine albumin and is activated to plasmin within the urinary space by urokinase‐type plasminogen activator. This agrees with aberrant filtration across an injured glomerular barrier independent of the primary disease. Pure plasmin and urine samples containing plasmin activate inward current in single murine collecting duct cells. In this study, it is shown that human lymphocytes may be used to uncover the effect of urine plasmin on amiloride‐ and aprotinin‐sensitive inward currents. Data from hypertensive rat models show that protease inhibitors may attenuate blood pressure. Aberrant filtration of plasminogen and conversion within the urinary space to plasmin may activate γ ENaC proteolytically and contribute to inappropriate NaCl retention and oedema in acute proteinuric conditions and to hypertension in diseases with chronic microalbuminuria/proteinuria.